KAJIAN BENTUK KARAKTER RUANG TAMAN TINGKIR SEBAGAI RUANG TERBUKA HIJAU PERKOTAAN KOTA SALATIGA - Febriana Trivita Widayanti; Tjoek Suroso Hadi (Jurnal Planologi, 2017)
Governments of Salatiga City is being heavily – incessant increase open green space in order to apply the 30% region used as green open space. Tingkir Park is a form of implementation of the Government program by implementing various concepts in it such as Green Design, Green Open Space, Green Water, and Green Waste. Garden Tingkir can also be used as a playground and sport park equipped with facilities of his supporters so that this becomes the attraction of citizens to make use of the garden. A strong appeal in the region triggered the emergence of a wide range of user activity (public) space by utilizing a variety of spaces in the area Tingkir Park.  The goal of the research is going to do that is to find the character space of the area Tingkir park which is a new park strive Government Salatiga city and Office of Copyright works and Spatial Salatiga city to meet the needs open green space in the city who is now a visitor attraction capable of being of local people. The research uses qualitative descriptive method with the deductive approach of Phenomenology .There are two types of green open space in the Park area, namely Tingkir Park and Tingkir Green Corridor. Open green space Parks Tingkir is active open space and applying the concept of Green Design, Green Open Space, Green Water, and Green Waste. While the green corridors have elongated pattern following the road and serves as a shady, air, and absorption of pollutants. The character of the spaces the Park area was discovered through some Tingkir processes such as find sub themes, themes, and concepts. Sub themes found in the utilization of space in the Park area Tingkir. The theme of the Tingkir Park area  found as the lounge, waiting, playing, exercising, and selling. While the concept of identity in the form of categorized into plazas, playgrounds, garden design; the structure of the form of the waiting room, leisure, economy; and meaning in the form of relaxing space. The third component of the space character of area Tingkir Park formulating as the recreation space Keywords: Green Open Space, City Parks, Characters